High Piezoelectric Performance of KNN-Based Ceramics over a Broad Temperature Range through Crystal Orientation and Multilayer Engineering - Guangrui Lu; Yunting Li; Rui Zhao; Yan Zhao; Jiaqi Zhao; Wangfeng Bai; Jiwei Zhai; Peng Li (Molecules, 2024)
Uninterrupted breakthroughs in the room temperature piezoelectric properties of KNN-based piezoceramics have been witnessed over the past two decades; however, poor temperature stability presents a major challenge for KNN-based piezoelectric ceramics in their effort to replace their lead-based counterparts. Herein, to enhance temperature stability in KNN-based ceramics while preserving the high piezoelectric response, multilayer composite ceramics were fabricated using textured thick films with distinct polymorphic phase transition temperatures. The results demonstrated that the composite ceramics exhibited both outstanding piezoelectric performance (d33~467 ± 16 pC/N; S~0.17% at 40 kV/cm) and excellent temperature stability with d33 and strain variations of 9.1% and 2.9%, respectively, over a broad temperature range of 25–180 °C. This superior piezoelectric temperature stability is attributed to the inter-inhibitive piezoelectric fluctuations between the component layers, the diffused phase transition, and the stable phase structure with a rising temperature, as well as the permanent contribution of crystal orientation to piezoelectric performance over the studied temperature range. This novel strategy, which addresses the piezoelectric and strain temperature sensitivity while maintaining high performance, is well-positioned to advance the commercial application of KNN-based lead-free piezoelectric ceramics.